أثر الخلفيات العقدية والثقافية للمترجم في ترجمة معاني القرآن الكريم إلى لغات أخرى (الترجمات الصينية لمعاني القرآن الكريم نموذجا): The Effect of Belief and Cultural Backgrounds of the Translator in Translating the Meanings of the Holy Quran into Other Languages (Chinese Translations of the Meanings of the Quran as an Example) - Yu Long, Ma (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
When we talk about the role of interpreting the meanings of the Holy Quran for non-Muslims, we should not confine our discussion on the translation per se, but we should cover all aspects that related to it, includes the conditions of the translator, the fulfillment of the translation requirements, the translator educational background etc. It is in this sense; this research highlights the impact of the belief and cultural background of the translator through a critical study of several Chinese translations. The translations which have been carried out by some Chinese translators either non-Muslims or Muslim, some of them were found translated the meanings of the Qur'an out of their enthusiasm for Islam without having any proficiency in Arabic language and knowledge of Sharia and, some of them were related to the strayed Islamic group i.e. Qadianiyyah. Among the most important findings of this research is: the translations of non-Muslims to the meanings of the Qur'an are full of fraught and serious mistakes. It includes the ignorance of the Arabic language methods, the neglection of precise meanings of the Arabic words and the deviation of the Quranic text from its real intention. Furthermore, it mixed the beliefs of other religions in the translation. In the other hand, the weakness of Muslims translations, who were motivated by religious fervor, is they did not study Arabic language and the Sharia, their translation has relied on secondary references and their translations were full of with errors in both the faith and linguistic aspects. Eventually, the translations which made by the deviant Muslims are regarded as a tool for the destruction of Islam from within. The danger of it no less than the danger of orientalist translations which intend to distort Islam.